Analysis of obstacles to the biology learning process in SMAN 1 Rantau Utara, Labuhanbatu Regency - Remma Indriany; Ika Chastanti (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2022)
The obstacles in the biology learning process are curriculum implementation, syllabus development, competence, material mastery, learning methods, laboratories, learning media, teaching aids, learning evaluation, and learning motivation. This study aims to identify the obstacles faced by teachers in the biology learning process at SMAN 1 Rantau Utara, Labuhanbatu Regency using descriptive research with a qualitative approach. The research data were obtained by distributing questionnaires and interviews with statements about barriers in the study of biology. Data is processed in percentages. The diagram results show high walls from 78% of laboratories, 76% of the curriculum, 70% of methods, media, and evaluation, and 67% of teacher competence. Overall, the data collection results show that with high barriers, obstacles to implementing the biology learning process cover an average of 72%. The results of this study can be used as a reference for teachers in schools, especially biology to design learning activities that further stimulate students' creative processes. In addition, it is hoped that external education stakeholders in Indonesia will focus more on implementing better policies.Abstrak Hambatan dalam proses pembelajaran biologi berupa penerapan kurikulum, pengembangan silabus, kompetensi, penguasaan materi, metode pembelajaran, laboratorium, media pembelajaran, alat peraga, evaluasi pembelajaran, dan motivasi belajar. Penelitian ini bertujuan untuk mengidentifikasi hambatan yang dihadapi guru dalam proses pembelajaran biologi di SMAN 1 Rantau Utara, Kabupaten Labuhanbatu menggunakan penelitian deskriptif dengan pendekatan kualitatif. Hasil data diperoleh dengan menyebarkan kuesioner dan juga wawancara dengan pernyataan tentang hambatan dalam studi biologi. Data diproses dalam persentase. Hasil diagram menunjukkan hambatan  tinggi dari 78% laboratorium, 76% kurikulum, 70% metode, media dan evaluasi, kompetensi guru 67%. Secara keseluruhan, hasil pendataan menunjukkan bahwa dengan hambatan tinggi, hambatan pelaksanaan proses pembelajaran biologi meliputi rata-rata 72%. Hasil penelitian ini dapat dijadikan acuan bagi guru di sekolah, khususnya biologi untuk merancang kegiatan belajar yang lebih merangsang proses kreatif siswa. Selain itu, diharapkan pemangku kepentingan eksternal pendidikan di Indonesia agar semakin fokus dalam menerapkan kebijakan yang lebih baik.